Host-Cell Surface Binding Targets in SARS-CoV-2 for Drug Design - Maleksabet, Hanieh; Rezaee, Elham; Tabatabai, Sayyed A. (Current Pharmaceutical Design, 2022)
The ongoing pandemic of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) became a major public health threat to all countries worldwide. SARS-CoV-2 interactions with its receptor are the first step in the invasion of the host cell. The coronavirus spike protein (S) is crucial in binding to receptors on host cells. Additionally, targeting the SARS-CoV-2 viral receptors is considered a therapeutic option in this regard. In this review of literature, we summarized five potential host cell receptors, as host-cell surface bindings, including angiotensin-converting enzyme 2 (ACE2), neuropilin 1 (NRP-1), dipeptidyl peptidase 4 (DPP4), glucose regulated protein-78 (GRP78), and cluster of differentiation 147 (CD147) related to the SARS-CoV-2 infection. Among these targets, ACE2 was recognized as the main SARS-CoV-2 receptor, expressed at a low/moderate level in the human respiratory system, which is also involved in SARS-CoV-2 entrance, so the virus may utilize other secondary receptors. Besides ACE2, CD147 was discovered as a novel SARS-CoV-2 receptor, CD147 appears to be an alternate receptor for SARSCoV- 2 infection. NRP-1, as a single-transmembrane glycoprotein, has been recently found to operate as an entrance factor and enhance SARS Coronavirus 2 (SARS-CoV-2) infection under in-vitro. DPP4, which was discovered as the first gene clustered with ACE2, may serve as a potential SARS-CoV-2 spike protein binding target. GRP78 could be recognized as a secondary receptor for SARS-CoV-2 because it is widely expressed at substantially greater levels, rather than ACE2, in bronchial epithelial cells and the respiratory mucosa. This review highlights recent literature on this topic.
Keywords: COVID-19